Impact of Behavioral Factors on Stock Market Investment Decisions among Young Investors in Biratnagar - Kafle, Niroj; Sah, Rahul Kumar (International Research Journal of MMC, 2026)
The study analyzes the impact of behavioral factors on stock market investment decisions among young investors in Biratnagar. The study examines the relationship between the behavioral factors (anchoring bias, risk propensity, herding behaviour, overconfidence bias), financial literacy and investment decision. The study was based on quantitative research design which used descriptive and explanatory research based on primary data collected among the young investors of stock market. The sample size of study compromised 200 respondents, The data were collected through the survey using the Google Form. The data analysis was performed with use of IBM SPSS Statistics 27 software. The data analysis consisted of demographic analysis, descriptive analysis, reliability tests, correlation analysis and regression analysis.The result of the study shows minimum threshold of reliability for each variable and overall reliability was maintained i.e. greater than 0.70. The study shows a positive relationship among overconfidence bias (β = 0.332, p < 0.001), financial literacy (β = 0.320, p < 0.001), and anchoring bias (β = 0.157, p < 0.05) with investment decision. But in contrast risk propensity (β = −0.011, p > 0.05) and herding behavior (β = 0.060, p > 0.05) shows statistically insignificant relationship with investment decision. The study suggests the young investors are more concerned with cognitive and informational factors making investment decision.